Review article about ELECTROCARDIOGRAM (ECG) - Hajer Maki Ali Khalil; Athmar jamal khalaf Hamza; Haneen Ammar Moussa Dawood (American Journal of Botany and Bioengineering, 2025)
The electrocardiogram (ECG) is a crucial medical device for monitoring heart activity and detecting cardiovascular abnormalities. Despite advancements, traditional ECG devices often rely on non-rechargeable batteries, limiting their efficiency and long-term use. This study addresses the knowledge gap by integrating a rechargeable lithium battery and wireless Bluetooth technology into an ECG system for improved portability and real-time data transmission. A prototype was developed using Arduino, heart rate, temperature, and SpO2 sensors, enabling efficient monitoring. The findings indicate that the modified ECG device provides accurate heart rate and oxygen saturation readings while enhancing accessibility and ease of use. The results suggest that such innovations can improve remote patient monitoring, particularly in home-care settings. Future work includes optimizing energy consumption through solar power integration.